Pengaruh Komunikasi Interpersonal dan Pemanfaatan Teknologi Informasi Terhadap Kinerja Pegawai Dinas Pemberdayaan Masyarakat dan Desa - Agung, Dhewa Brillian (Prodi Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik USB YPKP, 2024)
This research analyzes the influence of interpersonal communication and the use of information technology on the performance of employees in the community and village empowerment service in Rejang Lebong Regency. Using quantitative methods and data from 40 respondents, the results of multiple linear regression analysis show that interpersonal communication has a negative influence on employee performance. Meanwhile, the use of information technology has a positive effect. These results indicate that increasing interpersonal communication and the use of information technology contributes to improving employee performance at DPMD. However, it should be noted that these results need to be considered in a broader context by considering other factors that influence employee performance. It is hoped that this research can contribute to improving employee performance in an organization.